Summer soil moisture-convective precipitation coupling in Northern China at different timescales - Hongwei Yang; Zesu Yang; Hang He (Journal of Hydrology: Regional Studies)
Land-atmosphere coupling plays an important role in regional precipitation and climate change, but the coupling characteristics at different time scales remain controversial. This study uses ERA5 reanalysis data from 1970 to 2023 to examine how soil moisture impacts precipitation at different timescales. The focus is on the influence of soil moisture on sensible and latent heat fluxes, which regulate the lifting condensation level (LCL) and boundary layer height (BLH).The results show a generally positive coupling between soil moisture and rainfall intensity in Northern China. Soil moisture and precipitation were generally positively correlated, with little variation in the area of positive coupling on the monthly and annual scales, which were both larger than on the daily scale, but were strongest on the annual scale in terms of coupling strength. Soil moisture tends to be drier than normal during precipitation events. The strongest coupling along the soil moisture-latent heat flux-LCL/BLH pathway occurs on the annual timescale. Latent heat flux has a stronger influence on LCL than BLH at all timescales. Along the soil moisture-sensible heat flux-LCL/BLH pathway, the strongest coupling occurs on the monthly timescale. On a daily scale, sensible heat flux has a greater impact on BLH in the western region and on LCL in the eastern region. On monthly and annual timescales, sensible heat flux has a greater propensity to affect LCL. These findings improve our understanding of how soil moisture influences precipitation at various timescales, and provide valuable insights for improving numerical simulations of land-atmosphere interactions over northern China.